PENGARUH KONSENTRASI PUPUK BIO ORGANIK PLUS DAN UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TIMUN SURI (Cucumis sativus L.) - Muhamad Syarif; T. Rosmawaty; Selvia Sutriana (UIR Press, 2017)
The purpose of this study was to look at the effect of organic plus and urea biofertilizers on the growth and yield of (Cucumis sativus L.) interactively or primarily. The experimental design used was factorial Completely Randomized Design (RAL) consisting of 2 factors. The first factor is the provision of Bio-Organic Plus (P) fertilizer which consists of 4 levels, namely: 0, 2,5, 5, 7.5 cc / l water and the second factor is the administration of Urea (U) fertilizer which consists of 4 levels, namely: 0, 1,87, 3,75 and 5,62 g / plant. The parameters observed were an age of flowering, age of harvest, number of fruit crops, fruit weight and fruit weight. The results showed that the interaction of bio-organic plus and urea fertilizers significantly affected the number of fruits per plant, fruit weight per fruit and fruit weight per Suri cucumber plant. The best treatment is a combination of bio-organic fertilizer plus 7,5 cc / l water and urea fertilizer 3,75 g / plant (P3U2). In particular, the provision of bio-organic fertilizer plus significantly affected flowering age, harvest age, number of fruit crops, fruit weight and fruit weight. The best treatment is the administration of bio-organic fertilizer plus 7,5 cc / l water (P3). In particular, the administration of urea significantly affected flowering age, harvest age, number of fruit crops, fruit weight and fruit weight. The best treatment is giving urea fertilizer 3,75 g / plant (U2).